2018
DOI: 10.1002/cphc.201701235
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of Enzyme Immobilization Strategies for Glucose Biosensing in Real‐Time Using Fast‐Scan Cyclic Voltammetry Coupled with Carbon‐Fiber Microelectrodes

Abstract: Electrochemical monitoring of non-electroactive species requires a biosensor that is stable and selective, with sensitivity to physiological concentrations of targeted analytes. We have combined glucose oxidase-modified carbon-fiber microelectrodes with fast-scan cyclic voltammetry for real-time measurements of glucose fluctuations in brain tissue. Work presented herein quantitatively compares three approaches to enzyme immobilization on the microelectrode surface-physical adsorption, hydrogel entrapment, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…The long-term stability of such µ-electrodes was possibly due to strong chemical bonding between BQ-CS and GOx through free amines of lysine residues on the enzyme to the CS-matrix. Smith et al, 2018; demonstrated and confirmed that GOx immobilization by entrapment in a CS-hydrogel is another effective method for µ-electrode fabrication, which can be used for the measurements of brain glucose. Researchers combined GOx-modified carbon-fiber µ-electrodes with fast-scan voltammetry (CV) for real-time measurements of glucose in brain tissues [95].…”
Section: Microelectrode Arrays/printingmentioning
confidence: 81%
See 1 more Smart Citation
“…The long-term stability of such µ-electrodes was possibly due to strong chemical bonding between BQ-CS and GOx through free amines of lysine residues on the enzyme to the CS-matrix. Smith et al, 2018; demonstrated and confirmed that GOx immobilization by entrapment in a CS-hydrogel is another effective method for µ-electrode fabrication, which can be used for the measurements of brain glucose. Researchers combined GOx-modified carbon-fiber µ-electrodes with fast-scan voltammetry (CV) for real-time measurements of glucose in brain tissues [95].…”
Section: Microelectrode Arrays/printingmentioning
confidence: 81%
“…Smith et al, 2018; demonstrated and confirmed that GOx immobilization by entrapment in a CS-hydrogel is another effective method for µ-electrode fabrication, which can be used for the measurements of brain glucose. Researchers combined GOx-modified carbon-fiber µ-electrodes with fast-scan voltammetry (CV) for real-time measurements of glucose in brain tissues [95]. The detection range of the sensor was from 0.2 to 50 mM glucose in vitro using the flow-injection apparatus.…”
Section: Microelectrode Arrays/printingmentioning
confidence: 81%
“…Functions in the brain are regulated by neurotransmission events at the subsecond scale, which is why neuroscientists rely on electrochemical methods to detect instantaneous changes in neurotransmitters in vivo. [200] Biosensors utilize these electrochemical methods to monitor non-electroactive molecules [201] with precise, rapid, and continuous measurements of metabolites in situ. [202] While alternative methods such as nuclear magnetic resonance and microdialysis have limitations in spatial and temporal resolutions, the electrodes of electrochemical sensors can be placed directly in target tissues for real time monitoring and convert the analytes at the electrode site within seconds for fast response times.…”
Section: Neural Biosensors In Vivomentioning
confidence: 99%
“…[205,206] Subjecting the electrode to a potential drives a redox reaction process, with the resulting current being proportional to the concentration of the target analyte electrolyzed. [201] In 1962, Clark and Lyons were the first group to develop a glucose oxidase enzyme based electrode for detecting glucose and hydrogen peroxide (H 2 O 2 ). [207] Fast scan cyclic voltammetry (FSCV) is another detection method which can distinguish between the target analyte and interfering molecules.…”
Section: Neural Biosensors In Vivomentioning
confidence: 99%
“…c Illustration of the preparation of IPNs hydrogel (reprinted with permission from Ref. [19]) a more consistent active surface, thus improve the catalytic efficiency and avoid loss [24]. For higher activity, on the one hand, increase the available covalent bonding sites by introducing some monomers rich in -NH 2 and -COOH via 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) by forming amide bonds between the amine groups and carboxyl groups [25][26][27][28][29] or glutaraldehyde via covalent attachment to amino-actived polymers [30][31][32][33][34]; on the other hand, increase the specific surface area using microcapsules as Fig.…”
Section: Preparation Based On Catalytic Oxidation Sensitive Patternmentioning
confidence: 99%